Investigating Bedrock Controls on Erosional Retreat of the Blue Ridge Escarpment, Old Fort, North Carolina - Lila Anderson-Varga (UNC Test Journal, 2024)
The Blue Ridge Escarpment is a steep topographic boundary that in North Carolina separates the Blue Ridge Mountains from the Piedmont. Due to its steep topography, landslides are a common occurrence along it and result in erosional retreat of the escarpment. In order to better assist during landslide events, the North Carolina Geological Survey (NCGS) has been working on mapping landslides across western North Carolina. To assist the NCGS, this project mapped landslides around the escarpment near Old Fort and evaluated the risk based on bedrock structures. Field work occurred from the Spring of 2023 to the early Spring of 2024. Orientations of faults, foliations, and joint fractures were collected in the field. Landslides were identified in the field and from high-resolution LiDAR data. Bedrock structures were plotted on stereonets to assess their contributions to landslides. The foliations dominantly dip toward the SE. The orientation of the joints are a bit more sporadic, however; the majority strike NW/SE, consistent with regional jointing due to the Mesozoic rifting of Pangea. The E/W striking joints are likely associated with the Swannanoa Lineament. The data shows that planar failures along the foliation planes are the most common cause of landslides. While planar failures are more common in this case, there are two areas in Old Fort that have an impending wedge failure between the foliation and joints. In conclusion, this study shows that due to the potential for landslides by planar failure, slopes that dip in the same direction as the foliation are particularly at risk. Furthermore, joints associated with the Swannanoa Lineament play a role in erosional retreat of the escarpment.